Biosorption of heavy metal ions by the cell walls of yeast Saccharomyces cerevisiae in their combined presence - Aronbaev Sergey; Aronbaev Dmitry (E3S Web of Conferences, 2023)
By the stationary method ions biosorption Pb(II), Cd(II) and Cu(II) in di-and tri- ionic systems is studied. It is shown that the presence of extraneous ion in solution leads to a reduction (inhibition) of biosorbent sorption capacity. It is set that ion Pb (II) has the best adsorption capacity as in the case of individual ions, and in di- and tri-ionic systems. The explanation of this phenomenon from the point of the Lewis-Pearson theory of the nature of the specific binding of “hard” and “soft” ion-complex with the appropriate ligands - unctionally active groups of biopolymers budding fungi cell walls is given. It is offered that the relative electronegativity of the element on the Pauling scale can be an indicator of the relative sorption capacity of heavy metal ions.